PENERAPAN RASIO 9:16 DALAM PRODUKSI IKLAN LAYANAN MASYARAKAT PENCEGAHAN STUNTING - Wiguna, I Gede Juniartha Pratama; Yasa, Desak Putu Yogi Antari Tirta; Dwiyani, Ni Kadek (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
The production of community service advertisements entitled "Prevention of Stunting" was created with the aim of providing an understanding to the public about the dangers of stunting. This public service advertisement told tell you what are the causes of stunting, food solutions, and also what government programs are in progress. Social media is a platform that provides easier access to a wider community. This community service advertisement was made with several stages, namely ideas and then development for reliable observed for data. The work creation process involves partners and institutions in order to create works that have continuous benefits. This community service advertisement with the theme of stunting prevention can be one of the choices of advertising work that is able to package stories and information in an attractive format, namely in the form of Community Service Advertisements.